Bulk Bi-Sb polycrystals underpinned by high electron/phonon mean free path ratio enabling thermoelectric cooling under 77 K - Xiaowei Wu; Zhen Fan; Hangtian Zhu; Tianyu Wang; Meng Liu; Jun Li; Nan Chen; Qiulin Liu; Zhen Lu; Guodong Li; Xin Qian; Te-Huan Liu; et al. (Nature Communications)
Abstract Bi-Sb alloy, as a promising thermoelectric material at cryogenic temperatures, has seen stagnant progress due to challenges in understanding the transport behaviors of energy carriers, and difficulties in synthesizing high-homogeneity, large-grain samples. In this study, an inherent electron-phonon decoupling in Bi-Sb is revealed using the first-principles calculations based on the virtual crystal approximation. The mean free path of the dominant electrons (λ ele ~ 103 nm) is found of two orders of magnitude larger than that of phonons (λ ph ~ 101 nm), suggesting that a grain size greater than 10 μm would be favorable for thermoelectric transport. Bulk Bi-Sb polycrystals with highly elemental homogeneity and large grain size (~80 μm) are successfully synthesized through an ultra-fast quenching method combined with annealing, delivering superior thermoelectric performance. A prototype module based on the Bi0.88Sb0.12 polycrystal, with a ZT max of 0.48 at 150 K, is fabricated and demonstrates a ΔT max of 4 K at a T h of 75 K. This marks the first report of n-p paired thermoelectric cooling modules operating below liquid nitrogen temperature.